Lanting House preservation based on river culture in Sasirangan Village, Banjarmasin - Aula Sekar Arum Pertiwi; Agung Murti Nugroho (Civil and Environmental Science Journal (CIVENSE), 2023)
The shift in time has brought about changes that clearly leave the cultural identity of the archipelago. Sasirangan Village is one of the villages located in the middle of Banjarmasin City. This village still has a strong atmosphere, especially in the diversity of architecture in the area. River culture is still visible in this village, both for daily needs and also land for housing, namely Rumah Lanting. There are 3 Lanting houses in Sasirangan Village. The lack of a number of Lanting Houses left at this time raises a concern that there is a threat of extinction from cultural heritage. In this case, it is necessary to have a study of the architectural concept of the Lanting House to determine the right steps in preserving the Lanting House. The results of this study found that the right effort to preserve the Lanting House in Sasirangan Village was a revitalization effort that did not require material replacement and developed it as a Sasirangan gallery or souvenir shop that supports local wisdom and the identity of Sasirangan Village.